THE USE OF ZOOM MEETING IN LEARNING ENGLISH SPEAKING - Rini Yunianti Siregar; Ahmad Talib; Maemuna Muhayyang (State University of Makassar, 2023)
The purpose of this study is to describe the use of Zoom Meeting in learning English speaking and to find out students' perceptions of Zoom Meeting in learning English speaking. The researcher applies qualitative descriptive methods. The datum of this research collected through questionnaires and interviews. The subjects of this study are the lecturer who teaches Interactive Speaking, and 30 students from the Department of English Education, Faculty of Languages and Literature, Universitas Negeri Makassar for the 2021/2022 academic year. The results of data analysis found that (1) the use of the Zoom Meeting application, especially for its features, is able to help the lecturer and the students in the teaching and learning process in English speaking and has a positive impact on users, namely in terms of benefits (Perceived Usefulness), ease (Perceive Ease Of Use), and attitude (Attitude Toward Using) (2) students explanations in interviews regarding the perception of using Zoom Meeting in speaking English that Zoom Meeting is a good online learning tool because it has features that support English speaking learning during a pandemic. Despite the pandemic, students can still learn to speak English because in Zoom Meetings students and the lecturer can still interact and discuss well. From the two results of the two research statements above, it can be concluded that the use of Zoom Meeting in learning English speaking provides convenience in the teaching and learning process and also has a positive impact, especially on students' English speaking ability.Keywords— Zoom Meeting, English Speaking, Students’ Perception